National Health Interview Survey, 1988: Occupational Health Supplement ([Verlag nicht ermittelbar], 1993)
The basic purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. Each year, the National Center for Health Statistics conducts the NHIS, a personal interview household survey that uses a nationwide sample of the civilian, noninstitutionalized population of the United States. The NHIS includes a core set of questions that remains virtually unchanged across years on a variety of sociodemographic and health-related concerns. In addition, one or more current health topics is selected for special emphasis annually. For this supplement on occupational health, adult sample persons were asked questions regarding their lifetime working status and their work experience in the year prior to the interview. The primary focus of the supplement was on those individuals who had worked at civilian jobs in the prior year. These persons were asked about work-related injuries, back pain, hand discomfort, skin conditions, eye, nose, and throat irritations, health conditions, and smoking. Those who had previously worked, but not in the prior year, were asked questions about lifetime work experience, and then skipped to the questions on chronic conditions and smoking. Sample persons whose work during the prior year was active military duty also followed this sequence of questions. Those who had never worked were only asked about smoking. This collection also contains data from the basic questionnaire (see NATIONAL HEALTH INTERVIEW SURVEY, 1988 [ICPSR 9412]), including age, sex, race, marital status, education, veteran status, income, family relationship, self-reported health status, and activity limitations, and the number of bed days, doctor visits, and hospital stays in the previous year.